The Influence of The Competence of Apparatus and Information Systems on Public Political Participation in the Election of Regional Heads of The Covid-19 Pandemic Era - Afif Syarifudin Yahya (Journal of Social Science, 2021)
Regional head elections are one of the instruments to realize the implementation of democratic regional government because the community can directly choose the desired candidate to lead the implementation of government in the future. This research method is used combined research approaches (mixed methods), namely quantitative research approaches and qualitative research